EFFECT OF DIFFERENT GLUCOSE BLOOD LEVELS ON THE DEVELOPMENT OF CARDIOVASCULAR DISEASES AND COMPLICATIONS - E. V. Akhmedova; Z. A. Toguzova; M. N. Mamedov (Столичная издательская компания, 2015)
Diabetes mellitus (DM) is one of the health and social problems of modern health care. The main causes of death in patients with DM are macrovascular complications. Intensive hypoglycemic therapy is recommended to prevent complications; however it can increase the risk of severe hypoglycemia with subsequent growth rate of mortality. Glucose blood levels should be monitored to reduce the risk of cardiovascular disease and death, as well as control of normoglycemia and risk factors are needed. DM pathogenesis and prevalence are considered, and effects of glucose blood level on its outcomes are analyzed.